Osteogenic Enhancement Between Icariin and Bone Morphogenetic Protein 2: A Potential Osteogenic Compound for Bone Tissue Engineering - Xin Zhang; Xin Zhang; Xingnan Lin; Tie Liu; Tie Liu; Liquan Deng; Yuanliang Huang; Yuelian Liu (Frontiers Media S.A., 2019)
Icariin, a typical flavonol glycoside, is the main active component of Herba Epimedii, which was used to cure bone-related diseases in China for centuries. It has been reported that Icariin can be delivered locally by biomaterials and it has an osteogenic potential for bone tissue engineering. Biomimetic calcium phosphate (BioCaP) bone substitute is a novel drug delivery carrier system. Our study aimed to evaluate the osteogenic potential when Icariin was internally incorporated into the BioCaP granules. The BioCaP combined with Icariin and bone morphogenetic protein 2 (BMP-2) was investigated in vitro using an MC3T3-E1 cell line. We also investigated its efficacy to repair 8 mm diameter critical size bone defects in the skull of SD male rats. BioCaP was fabricated according to a well-established biomimetic mineralization process. In vitro, the effects of BioCaP alone or BioCaP with Icariin and/or BMP-2 on cell proliferation and osteogenic differentiation of MC3T3-E1 cells were systematically evaluated. In vivo, BioCaP alone or BioCaP with Icariin and/or BMP-2 were used to study the bone formation in a critical-sized bone defect created in a rat skull. Samples were retrieved for Micro-CT and histological analysis 12 weeks after surgery. The results indicated that BioCaP with or without the incorporation of Icariin had a positive effect on the osteogenic differentiation of MC3T3-E1. BioCaP with Icariin had better osteogenic efficiency, but had no influence on cell proliferation. BioCap + Icariin + BMP-2 showed better osteogenic potential compared with BioCaP with BMP-2 alone. The protein and mRNA expression of alkaline phosphatase and osteocalcin and mineralization were higher as well. In vivo, BioCaP incorporate internally with both Icariin and BMP-2 induced significantly more newly formed bone than the control group and BioCaP with either Icariin or BMP-2 did. Micro-CT analysis revealed that no significant differences were found between the bone mineral density induced by BioCaP with icariin and that induced by BioCaP with BMP-2. Therefore, co-administration of Icariin and BMP-2 was helpful for bone tissue engineering.